A Conceptual Model of the Impact of Management Information System Implementation on Organizational Behavior: The Mediating Roles of Communication, Job Satisfaction, and Leadership - Humaeriyah, Hani; Javed, Muhammad; Aghnia, Nadya Larasati (Journal of Organizational and Human Resource Development Strategies, 2025)
This paper presents a conceptual model that investigates the influence of Management Information System (MIS) implementation on organizational behavior, with a focus on the mediating roles of communication, job satisfaction, and leadership. As organizations increasingly rely on digital systems to streamline operations, understanding the human behavioral impacts of such systems becomes essential. This study posits that MIS alone does not guarantee improved organizational performance unless it is accompanied by effective internal communication, motivated and satisfied employees, and visionary leadership. By reviewing and synthesizing findings from existing literature, the model illustrates how these three mediating factors enable the successful translation of MIS capabilities into positive employee attitudes, productive interpersonal interactions, and enhanced organizational cohesion. The paper adopts a literature-based conceptual approach, offering a comprehensive theoretical framework that bridges technology and behavior. It aims to guide future empirical research by highlighting key behavioral variables that influence the success of MIS integration. The findings underscore the importance of aligning technological change with organizational culture and human capital strategies. This model serves not only as a foundation for scholarly inquiry but also as a practical reference for managers and policymakers aiming to maximize the behavioral and operational benefits of MIS implementation.